How far out of the way will we travel? Built environment influences on route selection for bicycle and car travel. - Winters, Meghan; Teschke, Kay; Grant, Michael; Setton, Eleanor M.; Brauer, Michael (Transportation Research Board of the National Academies, 2010)
Current travel demand models are calibrated for motorized transportation and do not perform as well for nonmotorized modes. Little evidence exists on how much, and for what reasons, the routes people travel deviate from the shortest-path or least-cost routes generated by transportation models. This paper investigates differences in total distance, road type used, and built environment features for shortest-path routes versus actual routes for utilitarian bicycle trips (n = 50) and car trips (n = 67) in Metro Vancouver, Canada. Bike trips were, on average, 360 m longer than the shortest possible route; car trips were 540 m longer. Regardless of mode, people do not detour far off the shortest route: detour ratios (actual distance/shortest distance) were similar, with three-fourths of trips within 10% of the shortest distance and at least 90% within 25%. Differences in the built environment measures en route suggest why bike commuters chose to detour: the actual routes had significantly more bicycle facilities (traffic-calming features, bike stencils, and signage) than did the shortestpath routes. Compared with shortest-path routes, cyclists spent significantly less of their travel distance along arterial roads and significantly more along local roads, off-street paths, and routes with bike facilities. As expected, car trips were more likely to be along highways and less likely to be along local roads than predicted by the shortest route. The results illustrate factors that might be included in travel models to more accurately model nonmotorized transportation and provide guidance for how dense bike facilities need to be when infrastructure to support cycling is designed. The article can be downloaded: DOI 10.3141/2190-01 (http://trb.metapress.com/content/9838q163rku54ul8/fulltext.pdf)
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsmittelwahl; Verkehrsplanung; Verkehrsmodell; Wegelänge; Routenwahl; Fahrradinfrastruktur; Radverkehrsanlage; Studie